DEVELOPMENT OF STONE FLAKE ARTIFACT TECHNOLOGY IN THE EARLY HALF OF HOLOCENE AT LEANG BATTI, SOUTH SULAWESI: PERKEMBANGAN TEKNOLOGI ARTEFAK SERPIH BATU PADA PARUH AWAL HOLOSEN DI LEANG BATTI, SULAWESI SELATAN - Suryatman; Fakhri; Sardi, Ratno; Hakim, Budianto (BRIN, 2020)
Abstract Intensive research in prehistoric caves in South Sulawesi has shown the cognitive capability of Sulawesi inhabitants that might not be possessed by other explorers in Wallacea. In the early half Holocene, the ability shown was to modify the shale tool known as the Toalean techno-complex. However, the view of the development of stone artifact technology in the period between before and early development of the Toalean techno-complex is rarely studied intensively. Leang Batti site is the occupation sites that can fill the information gap through the study of flakes artifact technology. 1376 artifacts were classified and analyzed for flakes by observing morphometric dynamics and tool type technology between the Early to Middle Holocene. The results that in the Early Holocene, the dominant technology was large flakes without modification. In the Middle Holocene, the size of the flakes began to change due to the influence of Toalean with the character of the modified flake technology began to enter in the basic concept of making tools, but not too strong. Abstrak Penelitian yang intensif di gua-gua prasejarah Sulawesi Selatan telah menunjukkan kemampuan kognitif penghuni Sulawesi yang mungkin jarang dimiliki populasi lain di Wallacea. Pada paruh awal Holosen kemampuan yang diperlihatkan adalah memodifikasi alat serpih yang dikenal dengan tekno-kompleks Toalean. Namun demikian, gambaran perkembangan teknologi artefak batu pada masa antara sebelum hingga awal perkembangan tekno-kompleks Toalean masih jarang diteliti secara intensif. Situs Leang Batti adalah situs hunian yang dapat mengisi kekosongan informasi melalui studi teknologi artefak serpih. Artefak berjumlah 1376 buah diklasifikasi dan dianalisis pada serpih dengan mengamati dinamika morfometrik dan teknologi tipe alat antara Holosen Awal hingga Tengah. Hasil penelitian menunjukkan bahwa pada Holosen Awal, teknologi yang dominan adalah serpih yang digunakan sebagai alat secara langsung tanpa dimodifikasi. Pada fase Holosen Tengah, ukuran serpih mulai mengalami perubahan karena pengaruh Toalean dengan karakter teknologi serpih yang dimodifikasi mulai masuk dalam konsep dasar sipembuat alat, namun tidak terlalu kuat.